Determinasi Perubahan Volume Air Terhadap Nilai Parameter Kualitas Air Pada Sumur Gali Masyarakat Di Kelurahan Fitu - Kota Ternate Selatan - Salnuddin Salnuddin; Nurhalis Wahidin; Halima Malaka; Nida Humaida; Muhammad Said Alhadad; Asmar Hi Daud (Jurnal Ilmu Lingkungan, 2025)
Groundwater quality degradation in small volcanic islands presents complex challenges for freshwater availability, particularly where communities heavily rely on groundwater resources. A study of groundwater dynamics in dug wells on Ternate Island, Indonesia, examined the relationship between water volume changes and water quality parameters while evaluating seawater intrusion potential through hydrostatic balance analysis. Researchers measured physical parameters (temperature, surface pressure) and chemical parameters (salinity, dissolved oxygen, electrical conductivity, total dissolved solids) in three sample wells and one coastal point. The analysis incorporated calculations of water volume changes, flushing rates, and regression analysis between water volume changes and water quality parameters to assess the dynamics of groundwater quality fluctuations. Water level changes showed a 27-minute lag after tidal shifts, with well 1 showing dominant volume changes during ebb tide (65%), while wells 2 and 3 were dominant during flood tide. Well 2 showed higher susceptibility to quality changes due to its lower flushing rate (13.7%) compared to well 1 (56.6%). Statistical analysis revealed that water volume increases did not significantly influence water quality changes (p > 0.05). These findings enhance our understanding of groundwater dynamics in volcanic islands and suggest that factors beyond water volume changes should be considered when managing groundwater resources in these settings. The research provides valuable insights for developing effective water resource management strategies in similar geological contexts worldwide.